Resolution of Conflict of Interest in Market Arrangement (Regulation of Modern Market Stalls Losari Kidul) - Cep Maulana; M. Deni Setiawan; Khaerudin Imawan; Rahmayanti Rahmayanti (International Journal Labs, 2025)
This study examines the effectiveness of persuasive communication in resolving stall layout conflicts at Losari Kidul Modern Market, Cirebon Regency. Conflicts arise due to the disorderly placement of traders' stalls that interfere with the comfort of visitors and cause unfair competition. The research uses a qualitative approach with observation, interview, and documentation methods, and integrates the Elaboration Likelihood Model (ELM) Theory and Fisher and Ury Conflict Resolution Theory. The results show that persuasive communication strategies, such as open discussion, mediation, and negotiation, are successful in improving traders' adherence to layout rules. The central path (logical argument) and peripheral path (emotional connection) approach in ELM has been shown to be effective in influencing trader behavior. In addition, mediation based on the principle of win-win solution has succeeded in creating a fair solution for all parties. This research provides academic contributions in the field of persuasive communication and conflict management, as well as practical recommendations for market managers to create an orderly and harmonious environment.